2017
DOI: 10.1038/cr.2017.62
|View full text |Cite
|
Sign up to set email alerts
|

Neurons secrete miR-132-containing exosomes to regulate brain vascular integrity

Abstract: Vascular integrity helps maintain brain microenvironment homeostasis, which is critical for the normal development and function of the central nervous system. It is known that neural cells can regulate brain vascular integrity. However, due to the high complexity of neurovascular interactions involved, understanding of the neural regulation of brain vascular integrity is still rudimentary. Using intact zebrafish larvae and cultured rodent brain cells, we find that neurons transfer miR-132, a highly conserved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
231
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(248 citation statements)
references
References 63 publications
5
231
1
Order By: Relevance
“…strong and linear effects) of expression in the surface defined by CAG-repeat lengths and age points in the striatum of these mice. This conclusion is reminiscent of a similar trend detected in the brain of wild-type mice, where miRNA regulation may be poorly correlated to gene expression signatures across cell types [38]. This conclusion is even more stringent for the cortex of Hdh mice, suggesting that miRNA regulation do not play a critical role in truly responding to HD in this brain area.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…strong and linear effects) of expression in the surface defined by CAG-repeat lengths and age points in the striatum of these mice. This conclusion is reminiscent of a similar trend detected in the brain of wild-type mice, where miRNA regulation may be poorly correlated to gene expression signatures across cell types [38]. This conclusion is even more stringent for the cortex of Hdh mice, suggesting that miRNA regulation do not play a critical role in truly responding to HD in this brain area.…”
Section: Discussionmentioning
confidence: 69%
“…Although we cannot exclude the possibility that the conclusion about a limited global role of miRNA regulation in the brain of Hdh mice might be biased by the current lack of cell-type specific RNA-seq data in HD mice, our data highlight a new set of precisely matched and highly prioritized miRNA-target relationships (see Figure 2, Table S3) that are known to play a role in neuronal activity and homeostasis. This feature applies to miRNAs that are upregulated in the striatum of Motif-Containing ProteinTrim26) is associated to brain vascular integrity in zebrafish [38], spine density [39] and synaptogenesis [40]. Knocking down Mir1b (upregulated and paired with Ventral Anterior Homeobox 2, Vax2) significantly alleviated neuronal death induced by hypoxia [41].…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal exosomes produced following neuronal activity were also taken up by astrocytes where GLT1 was up-regulated as a result, potentially via the indirect action of exosomal miR-124a [31]. Furthermore, neuronal miR-132 packaged into exosomes was found to be internalized by endothelial cells where it altered gene expression and regulated brain vascular integrity [35]. Taken together, these studies point towards a role of extracellular microRNAs in neuronal activity as well as brain development and maintenance.…”
Section: Contribution Of Extracellular Micrornas To Nervous System Fumentioning
confidence: 63%
“…They are actively secreted by healthy cells, including cells of the nervous system [31][32][33][34][35], and can be taken up by neighbouring cells or even other tissues, where they are functionally active [31,[36][37][38][39][40][41]. Hence, extracellular microRNAs have the potential to act as messengers over both short and long distances [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper in Cell Research, Xu and colleagues [11] used zebrafish as a model system to examine the function of miR-132, a microRNA predominantly expressed in neurons. By antagonizing miR-132 with morpholino antisense oligonucleotides, they surprisingly found that zebrafish larvae with inactivated miR-132 (miR-132 morphants) exhibited severe intracranial hemorrhage and impaired BBB integrity, as shown by extravasation of red blood cells and brain accumulation of exogenous circulating tracers.…”
mentioning
confidence: 99%